The heterogeneous impact of a successful tobacco control campaign: a case study of Mauritius. Issue 1 (15th March 2017) - Ross, Hana; Moussa, Leelmanee; Harris, Tom; Ajodhea, Rajive
Abstract : Background: Mauritius has one of the highest smoking prevalences in Africa, contributing to its high burden of non-communicable diseases. Mauritius implemented a series of tobacco control measures from 2009 to 2012, including tobacco tax increases. There is evidence that these policies reduced tobacco consumption, but it is not clear what impact they had across different socioeconomic groups. Method: The impact of tobacco control measures on different income groups was analysed by contrasting household tobacco expenditures reported in 2006–2007 and 2012 household expenditure surveys. We employed the seemingly unrelated regression model to assess the impact of tobacco use on other household expenditures and calculated Gini coefficients to assess tobacco expenditure inequality. Results: From 2006 to 2012, excise taxes and retail cigarette prices increased by 40.6% and 15.3% in real terms, respectively. These increases were accompanied by numerous non-price tobacco control measures. The share of tobacco-consuming households declined from 35.7% to 29.3%, with the largest relative drop among low-income households. The Gini coefficient of household tobacco expenditures increased by 10.4% due to decreased spending by low-income households. Low-income households demonstrated the largest fall in their tobacco budget shares, and the impact of tobacco consumption on poverty decreased by 26.2%. Households that continued purchasing tobacco reduced their expenditures on transportation, communication, health, and education. Conclusions: These results suggest that tobacco control policies, including sizeable tax increases, were progressive in their impact. We conclude that tobacco use increases poverty and inequality, but stronger tobacco control policies can mitigate the impact of tobacco use on impoverishment.